PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCUCIAN UANG MELALUI KEJAHATAN TINDAK PIDANA NARKOTIKA PUTUSAN NO. 311/Pid.Sus/2018/Pn.Mdn - Rahmayanti, Rahmayanti; Simarmata, Adrian Patric Presly; Buulolo, Taroni; br Siahaan, Masrani; Alfan, Yasser (JURNAL MUTIARA HUKUM, 2020)
The number of cases of money laundering in Indonesia certainly forces the government to tighten even more surveillance of suspicious transactions. Money laundering is often said to be a syndicate because the series is very organized, namely the perpetrators of these crimes each have the duty to disguise the proceeds of crime to be as if their legitimate assets. This money laundering research was conducted to determine the law enforcement of money laundering with narcotics crimes using secondary data, namely library materials and decisions with normative jurudical research types. TPPU has been regulated in Law No. 8 of 2010 concerning the prevention and eradication of money laundering, and narcotics law as an original crime, this law is expected to be able to guarantee justice and legal certainty and effectiveness in returning assets from the money laundering proceeds .